PENGARUH LIKUIDITAS TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN DAN DAMPAKNYA PADA EARNING RESPONSE COEFFICIENT - I Gusti Ayu Ratih Permata Dewi; Putu Diah Putri Idawati (Universitas Pendidikan Nasional, 2017)
This study aims to examine the effect of liquidity on timely delivery of financial statements and their impact on earning response coefficient companies in Indonesia, especially manufacturing companies. The timing of financial reporting means the availability of information in decision making before the information loses its capacity to influence decisions. Meanwhile, earnings response coefficient is strong market reaction to earnings information. This research is a quantitative research that is research that emphasizes on testing theory through measurement of research variables with numbers and perform data analysis with statistical procedure. The data used are external secondary data in the form of financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange 2013-2014. Selection of samples by purposive sampling method and obtained 50 companies with the number of observations for 2 years. Data analysis technique used is path analysis (path analysis). The test results show that liquidity has a positive effect on the timeliness of financial reporting and earning response coefficient. Furthermore, timely delivery of financial statements mediates the effect of liquidity on earning response coefficient. Direct coefficient of coefficient effect of liquidity on earnings response coefficient through timely delivery of financial statements gives greater effect than the coefficient value of indirect effect liquidity lever on earning response coefficient.Keywords: liquidity, timeliness, earning response coefficient.